Pendapatan Pedagang Pakaian Pasar Tradisional Dalam Menghadapi Fo (Factory Outlet) (Studi di Pasar Benjeng Desa Bulurejo Kecamatan Benjeng Kab. Gesik) - Norma Dia Bela (Universitas Muhammadiyah Gresik, 2020)
Background - Clothing traders in the Benjeng Traditional Market experienced a decrease in income when the existence of FO (Factory Outlet). The number of FO (Factory Outlet) that stands, Benjeng Traditional Market clothing traders still get income even though not as optimal as the time before the existence of FO (Factory Outlet). Objective - This study aims to examine the Income of Traditional Market Clothing Traders in Facing FO (Factory Outlet). Design : By collecting data from 7 informants and 1 key informant as a way for researchers to find accurate results. Data testing was performed using data analysis namely data reduction, data display, and conclusions. Findings - The results of data analysis about clothing merchant income in the face of FO (Factory Outlet) shows that the existence of Factory Outlets in the Benjeng Region can reduce the income of clothing traders even though the decline is not too large, but the defense of clothing traders in dealing with Factory Outlet is a form of welfare for the clothing traders in Benjeng Market, where this welfare is a main income, daily necessities and livelihood. In addition to the persistence of clothing traders in the Benjeng Market with the presence of Factory Outlets in the Benjeng Area there are things that traders must do so that buyers or customers are more interested in shopping at the Benjeng traditional market by increasing customer satisfaction by way of product innovation, service, price competition, and procedures product location. Research implications - With this research, it is hoped that the Benjeng Market clothing traders will continue to increase the efforts that must be made to provide the best for customers and buyers with the existence of a Factory Outlet in the Benjeng area. Research limitations - Researchers still have limitations in conducting this research, namely, the research setting only uses clothing traders in traditional markets so that researchers can only get data from clothing merchant informants.